Optimization of Laccase Activity Measurement in a Crude Oil Polluted Soil - Edemhanria, Lawrence; Shafe, Ruth O.; Osubor, Christopher C. (Polish Journal of Natural Sciences, 2021)
The effect of substrate concentration, soil incubation buffer volume and substrate incubation duration on laccase activity in a crude oil polluted soil were evaluated in this study. These parameters were studied over a specified range of values; substrate concentrations: 1, 5, 10, 15, 20 and 25 mM; soil incubation buffer volume: 25, 50, 75, 100 and 125 mL; and incubation duration: 30, 60, 90, 120 and 150 min. Laccase activity was evaluated by spectrophotometric method using pyrogallol as substrate. The optimum values of laccase activity in micromole per hour per gram soil [µmol/h/g] obtained were 2.80, 2.16 and 2.12 for the corresponding optimum substrate concentration (5 mM), soil incubation buffer volume (50 mL) and incubation duration (60 min) respectively. The use of these optimum values in laccase assay will provide a very useful indication of microbial metabolic activities during the process of bioremediation of the polluted soil.